Pengetahuan, Sikap, dan Perilaku Anak serta Lingkungan Rumah dan Sekolah dengan Kejadian Infeksi Kecacingan Anak Sekolah Dasar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Background: In some area the prevalence of intestinal, worm dissease is relatively high or more than 60%. Some research showed that the biggest prevalence was accuped in primary school children. Objectives: To investigate the relationships of knowledge and attitude toward intestinal worm infection